Smoking. Addiction that Causes more Deaths than AIDS - Emiliano Nicolás Diez y Martínez de la Cotera (Revista Finlay)
Some data are provided on the prevalence of smoking in the world, in Cuba and in the province as well as its consequences for health. We describe the direct link between smoking and some chronic diseases such as lung cancer and ischemic heart disease. Given that the Cuban government has expressed its political and legal will, gradually oriented to the eradication of this addiction, we urge the community to comply with legislations related to smoking control.